The Role of Accounting Information in Corporate Valuation Processes (gjstudies, 2019)
This research investigates the role of accounting information in corporate valuationprocesses through a novel methodological lens that integrates principles from computational linguistics and network theory. Traditional valuation research has predominantlyfocused on the predictive power of individual financial ratios or earnings metrics. Incontrast, this study proposes and validates a holistic framework that conceptualizes afirm’s entire set of disclosed accounting data as a complex, interconnected informationnetwork. We argue that the value-relevance of accounting information is not merely afunction of specific line items but emerges from the structural properties and relationaldynamics within this network. Our methodology involves parsing annual financialstatements into discrete informational nodes and modeling the explicit and implicitrelationships between them using graph-theoretic constructs. We then extract novelmetrics, such as informational centrality, coherence density, and explanatory path efficiency, to quantify the overall quality and integration of a firm’s accounting disclosureecosystem. Applying this framework to a longitudinal dataset of SP 500 firms from1995 to 2004, we find that these network-derived metrics significantly enhance theexplanatory power of valuation models beyond traditional accounting fundamentals.Specifically, firms with more coherent and centrally organized accounting informationnetworks exhibit lower valuation errors, reduced analyst forecast dispersion, and attenuated market mispricing around earnings announcements. Furthermore, we identify anonlinear relationship where the marginal benefit of additional accounting disclosurediminishes and can become negative if it excessively increases network complexitywithout improving coherence. These findings offer a paradigm shift from evaluatingaccounting information based on isolated components to assessing its architectural integrity, providing new tools for investors, standard-setters, and auditors to evaluatethe true decision-usefulness of financial reports.